1987
DOI: 10.1017/s0022215100101380
|View full text |Cite
|
Sign up to set email alerts
|

The nasal distribution of metered does inhalers

Abstract: The intranasal distribution of aerosol from a metered dose inhaler has been assessed using a radiotracer technique. Inhalers were prepared by adding 99Tcm-labelled Teflon particles (simulating the drug particles) to chlorofluorocarbon propellants, and scans of the head (and chest) taken with a gamma camera. Ten healthy subjects (age range 19–29 years) each performed two radioaerosol studies with the inhaler held in two different ways: either in a single position (vial pointing upwards) or in two positions (via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 7 publications
3
37
0
Order By: Relevance
“…Variations in technique apparently make little difference to the site of deposition in the nose. However good the technique, some 80% of the dose of a nasal aerosol is deposited in the anterior one-third of the nose and penetration is negligible beyond the narrow point known as the "nasal valve" (Newman et al 1987). In any case, site of placement by micropipette seems to make little difference to nicotine absorption (Johansson et at.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in technique apparently make little difference to the site of deposition in the nose. However good the technique, some 80% of the dose of a nasal aerosol is deposited in the anterior one-third of the nose and penetration is negligible beyond the narrow point known as the "nasal valve" (Newman et al 1987). In any case, site of placement by micropipette seems to make little difference to nicotine absorption (Johansson et at.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal aerosols (Newman et al 1987b ) that utilize propellants to generate the spray have been shown to have smaller droplets compared to conventional nasal sprays. However, the deposition pattern is even more localized because of the exit velocity of the plume.…”
Section: Nasal Physiologymentioning
confidence: 99%
“…And the total surface area of the nasal cavity is around 150 cm 2 [10] . The proportion of the ciliated epithelium that nasal spray reaches is able to be readily assessed by observing the proportion of nasal spray transported by mucociliary flow [11] . Berridge et al introduced a technique which utilizes positron emission tomography (PET) to measure the radioactivity of administered isotopes [12] .…”
Section: Discussionmentioning
confidence: 99%